Investigation of Hydromagnetic flow and heat transfer in a Boussinesq - Stokes suspension over an exponentially stretching sheet - Reddy, L Venkata; Chandrashekara, N P; G, Roopa (Journal of Neonatal Surgery, 2025)
The investigation of velocity profiles and heat transfer properties in a hydromagnetic Boussinesq-Stokes suspension (BSS) flow over an exponentially stretching impermeable sheet is presented in this paper. Partial differential equations are the fundamental formulas that control flow and heat transfer. A suitable local similarity transformation has been applied to convert the equations into nonlinear ordinary differential equations. The differential transform method (DTM) is used to obtain the series solutions of the transformed equations with guaranteed convergence. On velocity profiles and heat transfer, the influence of the Chandrasekhar number, couple stress parameter, Prandtl number, and Eckert number are examined. The conclusions are explained graphically.